Hikikomori in Japanese Community Perspective - Ngurah Indra Pradhana (Universitas Diponegoro, 2021)
This research is entitled “Hikikomori in Japanese Community Perspective”. Data was collected by distributing questionnaires to Kobe Women's University students. Through this research, several opinions from the Japanese community will be obtained regarding the understanding of Hikikomori. In this study, two concepts are used: the definition of Hikikomori and the definition of Anthropophobia. By the result, the definition of Hikikomori is as follows; someone who always shuts himself up in the house for a long time, , someone who is not connected with society, someone who is isolated because he doesn't have good relations with society, someone who doesn't work or attend school, and someone who depends on his parents for his life. The causes can be divided into two; internal and external. The causes from oneself (internal) include no desire to be involved with other people, unfamiliar with society, failure at work, feeling confused with the community environment, dissatisfaction with their personal life, lack of enthusiasm for life, not being good at communicating with others, has not found identity, rarely communicates with the outside world, does not fit in with people in society, stress, trauma, feel unprofitable or unfit for work or school, feels tired of social life, feels bored with social life, in his life, there are opportunities to self-isolate, embarrassed, feel like doing nothing, unstable physically and mentally, feel confused about public relations. Meanwhile, the causes from external parties include bullying, harassment, changes in community behaviour, and intimidation.